CFD-моделирование радиатора для воздушного охлаждения микропроцессоров в ограниченном пространстве - Трофимов, В.Е.; Павлов, А.Л.; Мокроусова, Е.А. (Технология и конструирование в электронной аппаратуре, 2016)
Проведено CFD-моделирование радиатора с компактной теплоотдающей поверхностью в виде тупиковых полостей, в которые втекают импактные воздушные струи. Получены тепло- аэродинамические характеристики и даны рекомендации по конструированию радиаторов такого типа для отвода тепла от микропроцессоров в ограниченном пространстве. Проведено CFD-моделювання радіатора з компактною поверхнею тепловіддачи у вигляді тупикових порожнин, у які втікають імпактні повітряні струмені. Отримано тепло-аеродинамічні характеристики і дано рекомендації щодо конструювання радіаторів такого типу для відводу тепла від мікропроцесорів в обмеженому просторі. One of the final stages of microprocessors development is heat test. This procedure is performed on a special stand, the main element of which is the switching PCB with one or more mounted microprocessor sockets, chipsets, interfaces, jumpers and other components which provide various modes of microprocessor operation. The temperature of microprocessor housing is typically changed using thermoelectric module. The cold surface of the module with controlled temperature is in direct thermal contact with the microprocessor housing designed for cooler installation. On the hot surface of the module a radiator is mounted. The radiator dissipates the cumulative heat flow from both the microprocessor and the module.High density PCB layout, the requirement of free access to the jumpers and interfaces, and the presence of numerous sensors limit the space for radiator mounting and require the use of an extremely compact radiator, especially in air cooling conditions. One of the possible solutions for this problem may reduce the area of the radiator heat-transfer surfaces due to a sharp growth of the heat transfer coefficient without increasing the air flow rate. To ensure a sharp growth of heat transfer coefficient on the heat-transfer surface one should make in the surface one or more dead-end cavities into which the impact air jets would flow. CFD simulation of this type of radiator has been conducted. The heat-aerodynamic characteristics and design recommendations for removing heat from microprocessors in a limited space have been determined.